Platelet Dysfunction and Thrombosis in JAK2V617F-Mutated Primary Myelofibrotic Mice. Issue 10 (October 2020) - Matsuura, Shinobu; Thompson, Cristal R.; Belghasem, Mostafa Elmokhtra; Bekendam, Roelof H.; Piasecki, Andrew; Leiva, Orly; Ray, Anjana; Italiano, Joseph; Yang, Moua; Merill-Skoloff, Glenn; Chitalia, Vipul C.; Flaumenhaft, Robert; et al.
Abstract : Objective: The risk of thrombosis in myeloproliferative neoplasms, such as primary myelofibrosis varies depending on the type of key driving mutation (JAK2 [janus kinase 2], CALR [calreticulin], and MPL [myeloproliferative leukemia protein or thrombopoietin receptor]) and the accompanying mutations in other genes. In the current study, we sought to examine the propensity for thrombosis, as well as platelet activation properties in a mouse model of primary myelofibrosis induced by JAK2 V617F (janus kinase 2 with valine to phenylalanine substitution on codon 617) mutation. Approach and Results: Vav1-hJAK2 V617F transgenic mice show hallmarks of primary myelofibrosis, including significant megakaryocytosis and bone marrow fibrosis, with a moderate increase in red blood cells and platelet number. This mouse model was used to study responses to 2 models of vascular injury and to investigate platelet properties. Platelets derived from the mutated mice have reduced aggregation in response to collagen, reduced thrombus formation and thrombus size, as demonstrated using laser-induced or FeCl3 -induced vascular injury models, and increased bleeding time. Strikingly, the mutated platelets had a significantly reduced number of dense granules, which could explain impaired ADP secretion upon platelet activation, and a diminished second wave of activation. Conclusions: Together, our study highlights for the first time the influence of a hyperactive JAK2 on platelet activation-induced ADP secretion and dense granule homeostasis, with consequent effects on platelet activation properties. Abstract : Supplemental Digital Content is available in the text.